2019
DOI: 10.1096/fj.201901537r
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 suppresses the NLRP3 inflammasome activation through inhibition of its assembly

Abstract: Ginsenoside Rg3 is one of the main constituents of Panax ginseng. Compelling evidence has demonstrated that ginsenoside Rg3 is capable of inhibiting inflammation.However, the mechanism mediating its anti-inflammatory effects remain unclear.Here we show that ginsenoside Rg3 blocks IL-1β secretion and caspase-1 activation through inhibiting LPS priming and the NLRP3 inflammasome activation in human and mouse macrophages. Rg3 specifically inhibits activation of NLRP3 but not the NLRC4 or AIM2 inflammasomes. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…Since Nlrp3 inflammasome activation is a multi-step process, inhibiting Nlrp3 inflammasome activation can be accomplished through several different means including: suppressing molecules that promote inflammasome activation or formation, silencing upstream signals, or by directly or indirectly inhibiting the inflammasome complex formation depending on the molecule targeted ( 10 , 72 ). Some of the direct inhibitors, which specifically target Nlrp3-Nlrp3, Nlrp3-Asc, or NEK7-Nlrp3 interactions, are ginsenoside Rg3, oridonin, and tranilast ( 73 75 ). Ginsenoside Rg3, isolated from Panax ginseng , specifically blocks IL-1β secretion and caspase-1 activation by inhibiting LPS priming and Nlrp3 inflammasome assembly ( 73 ).…”
Section: Nlrp3 Inhibition As a Therapeutic Intervention For Admentioning
confidence: 99%
See 1 more Smart Citation
“…Since Nlrp3 inflammasome activation is a multi-step process, inhibiting Nlrp3 inflammasome activation can be accomplished through several different means including: suppressing molecules that promote inflammasome activation or formation, silencing upstream signals, or by directly or indirectly inhibiting the inflammasome complex formation depending on the molecule targeted ( 10 , 72 ). Some of the direct inhibitors, which specifically target Nlrp3-Nlrp3, Nlrp3-Asc, or NEK7-Nlrp3 interactions, are ginsenoside Rg3, oridonin, and tranilast ( 73 75 ). Ginsenoside Rg3, isolated from Panax ginseng , specifically blocks IL-1β secretion and caspase-1 activation by inhibiting LPS priming and Nlrp3 inflammasome assembly ( 73 ).…”
Section: Nlrp3 Inhibition As a Therapeutic Intervention For Admentioning
confidence: 99%
“…Some of the direct inhibitors, which specifically target Nlrp3-Nlrp3, Nlrp3-Asc, or NEK7-Nlrp3 interactions, are ginsenoside Rg3, oridonin, and tranilast ( 73 75 ). Ginsenoside Rg3, isolated from Panax ginseng , specifically blocks IL-1β secretion and caspase-1 activation by inhibiting LPS priming and Nlrp3 inflammasome assembly ( 73 ). In contrast, oridonin, derived from Rabdosia rubescens , blocks inflammasome assembly and activation by hindering the NEK7-Nlrp3 interaction, which is crucial for Nlrp3 oligomerization and Asc recruitment to Nlrp3 ( 74 , 76 ).…”
Section: Nlrp3 Inhibition As a Therapeutic Intervention For Admentioning
confidence: 99%
“…For instance, ginsenosides Rg1, Rg3, Rh1, Rh3, Rb1, Rk1, and Rf from Panax ginseng C.A. Meyer have been demonstrated to exhibit dual actions against neuroinflammation and hyperactivation of the HPA axis [106,108,[206][207][208][209][210][211][212][213][214][215], while 3,6'-disinapoyl sucrose and the oligosaccharide esters-enriched fraction, YZ50, from Polygala tenuifolia Willd have been shown to possess bioactivity that de-hyperactivates the HPA axis [216][217][218]. Additionally, poricoic acid A, isolated from Poria cocos (Schw.)…”
Section: Chm Effects On the Neuroendocrine-immune Networkmentioning
confidence: 99%
“…Some promising selective inhibitors and medicines already used to treat other diseases are found to target various aspects of inflammasome activation regulated by NEK7. These inhibitors may disrupt the upstream events or directly regulate the expression or modification of NEK7 and NLRP3 thus effecting their interaction (Zhang Y. et al, 2017;He et al, 2018;Chiu et al, 2019;Wu et al, 2019;Liu D. et al, 2020;Shi et al, 2020).…”
Section: Inhibitors and Their Application To Diseasesmentioning
confidence: 99%
“…Importantly, a growing number of studies have suggested that some drugs, including natural products (traditional Chinese medicine) (He et al, 2018;Kim et al, 2019;Shi et al, 2020) and chemical medicines (Zhang et al, 2018;Chiu et al, 2019;Torp et al, 2019;Zhou et al, 2019), have emerging roles in inhibiting NEK7-related NLRP3 inflammasome activation with distinct regulatory mechanisms. The three natural products oridonin (He et al, 2018;Liu H. et al, 2020), artemisinin (Kim et al, 2019), and ginsenoside Rg3 (Shi et al, 2020) have been reported to have similar functions in abrogating NEK7-NLRP3 interaction, as corroborated by different mouse models (He et al, 2018;Kim et al, 2019;Shi et al, 2020). Seven chemical medicines, including glucosamine (Chiu et al, 2019), metformin (Zhou et al, 2019, glibenclamide (Liu H. et al, 2020), ALK inhibitors (ceritinib and lorlatinib) (Zhang et al, 2018), autophagy inhibitors (chloroquine and bafilomycin A1) (Torp et al, 2019), and 1,25(OH)2D3 (Cao et al, 2020), have also shown significant inhibitory effects on various aspects of the NEK7-NLRP3 interaction.…”
Section: Inhibitors and Their Application To Diseasesmentioning
confidence: 99%